Altered neural activation in ornithine transcarbamylase deficiency during executive cognition: An fMRI study. Issue 4 (23rd November 2011) - Gropman, Andrea L.; Shattuck, Kyle; Prust, Morgan J.; Seltzer, Rebecca R.; Breeden, Andrew L.; Hailu, Ayichew; Rigas, Amanda; Hussain, Rehan; VanMeter, John
Abstract Background: Ornithine transcarbamylase deficiency (OTCD) is an X‐linked urea cycle disorder characterized by hyperammonemia resulting in white matter injury and impairments in working memory and executive cognition. Objective: To test for differences in BOLD signal activation between subjects with OTCD and healthy controls during a working memory task. Design, setting and patients: Nineteen subjects with OTCD and 21 healthy controls participated in a case‐control, IRB‐approved study at Georgetown University Medical Center. Intervention: An N‐back working memory task was performed in a block design using 3T functional magnetic resonance imaging. Results: In subjects with OTCD we observed increased BOLD signal in the right dorsolateral prefrontal cortex (DLPFC) and anterior cingulate cortex (ACC) relative to healthy age matched controls. Conclusions: Increased neuronal activation in OTCD subjects despite equivalent task performance points to sub‐optimal activation of the working memory network in these subjects, most likely reflecting damage caused by hyperammonemic events. These increases directly relate to our previous finding of reduced frontal white matter integrity in the superior extents of the corpus callosum; key hemispheric connections for these areas. Future studies using higher cognitive load are required to further characterize these effects. Hum Brain Mapp, 2013. © 2011 Wiley Periodicals, Inc.